EVS35—International Electric Vehicle Symposium and Exhibition (Oslo, Norway) (MDPI - Multidisciplinary Digital Publishing Institute, 2025)
This Special Issue gathers the best papers from EVS36, the 36th International Electric Vehicle Symposium and Exhibition, which was held from 11 to 14 June 2023 in Sacramento, California, USA. The International Electric Vehicle Symposium (EVS) is the world's longest, largest, and highest-spec event in the field of electric vehicles, covering areas including pure electric vehicles, hybrid vehicles, fuel cell vehicles, and core components. With the support of the World Electric Vehicle Association, the symposium is hosted by three regional professional organizations under the World Electric Vehicle Association in North America (Electric Drive Transportation Association, EDTA), Europe (The European Association for Electromobility, E-Mobility Europe), and Asia (Electric Vehicle Association of Asia Pacific, EVAAP), in turn. EVS has already had a long history since its birth in Phoenix, Arizona, USA, in 1969. The theme of EVS36 is “The Electric Future is Here”. The papers cover research, market, and government activities across all fields related to hybrid, battery, and fuel cell technologies, associated infrastructure, and services. The authors of the best papers presented at EVS36 were invited to further extend their EVS36 paper, including their most recent research findings. After a second thorough round of peer review, these papers were published in this Special Issue of the World Electric Vehicle Journal (WEVJ), the official journal of the World Electric Vehicle Association (WEVA).